2018
DOI: 10.1039/c8ra08471h
|View full text |Cite
|
Sign up to set email alerts
|

Electrodegradation of 2,4-dichlorophenoxyacetic acid herbicide from aqueous solution using three-dimensional electrode reactor with G/β-PbO2anode: Taguchi optimization and degradation mechanism determination

Abstract: Optimization of process parameters using the Taguchi method, electrochemical degradation and electrochemical degradation mechanism of 2,4-D herbicide using 2D and 3D reactors with G/β-PbO2 anode were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…In order to overcome these drawbacks, some research proposes the use of three-dimensional (3D) electrodes. The direct oxidation of organic pollutants using 3D anodes is superior due to the larger contact surface and more active sites than 2D electrodes [23]. Evidently, to implement these 3D electrodes, a different mechanical design of the electrochemical cell is required, and recently, our group proposed a significantly efficient design in which the concepts of microfluidics and flow-through electrodes were properly merged [1][2][3][4]24] Given the above, this article studies the behavior of 2D, or 3D anodes (MMO-Ti/RuO2IrO2) synthesized employing a new heating technique using microwaves [17,25] in the electrolysis and photo-electrolysis of urine polluted with a mixture of antibiotics: Penicillin G (PENG), Meropenem (MEP) and Chloramphenicol (CLP).…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome these drawbacks, some research proposes the use of three-dimensional (3D) electrodes. The direct oxidation of organic pollutants using 3D anodes is superior due to the larger contact surface and more active sites than 2D electrodes [23]. Evidently, to implement these 3D electrodes, a different mechanical design of the electrochemical cell is required, and recently, our group proposed a significantly efficient design in which the concepts of microfluidics and flow-through electrodes were properly merged [1][2][3][4]24] Given the above, this article studies the behavior of 2D, or 3D anodes (MMO-Ti/RuO2IrO2) synthesized employing a new heating technique using microwaves [17,25] in the electrolysis and photo-electrolysis of urine polluted with a mixture of antibiotics: Penicillin G (PENG), Meropenem (MEP) and Chloramphenicol (CLP).…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of the decomposition ability of 2,4,5-T with some other results shows that the decomposition mechanism and the formation of intermediate compounds are carried out by OH • free radicals, and the degradation efficiency was almost the same according to the 2,4-D and phenol degradation efficiency. 25,34 Moreover, the high-voltage DC electrochemical engineering with plasma appearance on the iron electrode showed that the degradation ability of 2,4,5-T at the initial concentration of 30 mg L −1 achieved after 120 min was 71.17%, which was better than that of phenol at the initial concentration of 40 mg L −1 with 46% degradation in the same time of 120 min by pulsed high-voltage discharge technology. 18 In addition, the decomposition ability of 2,6-dichlorophenol at the initial concentration of 20 mg L −1 reached 95% by coaxial dielectric barrier discharge technology.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Porous reticulated vitreous carbon (RVC) with different porosities was also implemented as the support for PbO 2 , and it was found that the electrocatalytic behavior of RVC/PbO 2 for azo dye degradation was dramatically influenced by the porosity . Carbonaceous materials such as graphite (G) have been proposed and explored as an electrode matrix for the PbO 2 anode, and the PbO 2 film coated on the surface of the graphite shows remarkable stability. Carbon felt (CF) is considered as another promising substrate for electrodes due to its low cost, large surface area, good electrical conductivity, high porosity and three-dimensional structure, which contribute to • OH radicals produced at countless active sites. Three-dimensional CF was reported mostly as a cathode skeleton for perchlorate degradation .…”
Section: Introductionmentioning
confidence: 99%